Influenza vaccine effectiveness in older adults compared with younger adults over five seasons. Issue 10 (28th February 2018) - Russell, Kate; Chung, Jessie R.; Monto, Arnold S.; Martin, Emily T.; Belongia, Edward A.; McLean, Huong Q.; Gaglani, Manjusha; Murthy, Kempapura; Zimmerman, Richard K.; Nowalk, Mary Patricia; Jackson, Michael L.; Jackson, Lisa A.; et al.
Abstract: Background: There have been inconsistent reports of decreased vaccine effectiveness (VE) against influenza viruses among older adults (aged ≥ 65 years) compared with younger adults in the United States. A direct comparison of VE over multiple seasons is needed to assess the consistency of these observations. Methods: We performed a pooled analysis of VE over 5 seasons among adults aged ≥ 18 years who were systematically enrolled in the U.S. Flu VE Network. Outpatients with medically-attended acute respiratory illness (cough with illness onset ≤ 7 days prior to enrollment) were tested for influenza by reverse transcription polymerase chain reaction. We compared differences in VE and vaccine failures among older adult age group (65–74, ≥75, and ≥ 65 years) to adults aged 18–49 years by influenza type and subtype using interaction terms to test for statistical significance and stratified by prior season vaccination status. Results: Analysis included 20, 022 adults aged ≥ 18 years enrolled during the 2011–12 through 2015–16 influenza seasons; 4, 785 (24%) tested positive for influenza. VE among patients aged ≥ 65 years was not significantly lower than VE among patients aged 18–49 years against any subtype with no significant interaction of age and vaccination. VE against A(H3N2) viruses was 14% (95% confidence interval [CI] −14% to 36%) for adults ≥ 65 years and 21% (CI 9–32%) for adults 18–49 years. VE against A(H1N1)pdm09 was 49% (95% CI 22–66%) for adults ≥ 65 years and 48% (95% CI 41–54%) for adults 18–49 years and against B viruses was 62% (95% CI 44–74%) for adults ≥ 65 years and 55% (95% CI 45–63%) for adults 18–49 years. There was no significant interaction of age and vaccination for separate strata of prior vaccination status. Conclusions: Over 5 seasons, influenza vaccination provided similar levels of protection among older and younger adults, with lower levels of protection against influenza A(H3N2) in all ages.